Not in vain ; 10th what God hath wrought amongst the Kanakas in Queensland with appendix, containing, inter aha Report of the Queensland Kanaka Mission for the year 1895-96 (1896)
Contents includes : Queensland Kanaka Mission : Object and principles (revised).
Photocopy.
Keywords: Queensland Kanaka Mission; Brethren movement -- missions -- Australia -- history